2015
DOI: 10.1038/ajg.2015.192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abnormal Liver Function Tests in Celiac Disease and the Effect of a Gluten-Free Diet in the US Population

Abstract: Forty percent of individuals will have elevated LFTs at CD diagnosis; however, the majority will normalize with standard CD therapy. LFTs should be checked in all patients with CD and coexisting liver disorder should be considered in patients whose LFTs have not improved within a year on a GFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 40 publications
1
35
1
4
Order By: Relevance
“…For example, Farre and colleagues [33] reported increased ALT in 30% of children, Biase et al [34] in 38% and Bonamico et al in as many as 57% [16]. Similarly, in celiac adults Bardella et al found 42% [35] to have increased liver values, and in a recent study by Castelli et al this was seen in 41% [14]. Making the difference even more conspicuous, we used a rather low ALT value (30 U/l) for the upper limit of normal (ULN) instead of 40 U/l [34].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, Farre and colleagues [33] reported increased ALT in 30% of children, Biase et al [34] in 38% and Bonamico et al in as many as 57% [16]. Similarly, in celiac adults Bardella et al found 42% [35] to have increased liver values, and in a recent study by Castelli et al this was seen in 41% [14]. Making the difference even more conspicuous, we used a rather low ALT value (30 U/l) for the upper limit of normal (ULN) instead of 40 U/l [34].…”
Section: Discussionmentioning
confidence: 83%
“…The major reason for the improved diagnostic efficacy is recognition of the diversity of the clinical picture, including a variety of extra-intestinal symptoms [6,7]. One of the best-characterized of these is hypertransaminasemia [8][9][10][11], the prevalence of which in untreated adults has been up to 42% [12][13][14]. Only a limited number of studies have been conducted in children, but the percentages have been generally comparable to those reported in adults [9,15,16].…”
Section: Introductionmentioning
confidence: 80%
“…96 However, ~75% of patients with elevated liver enzymes in coeliac disease do not have a separate disorder and these individuals respond well to gluten withdrawal. 112 Whether hepatitis in these cases originates from crossreacting autoantibodies (as in dermatitis herpetiformis) or is initiated by a transfer of cytokines and other inflammatory mediators from the small bowel through the portal vein into the liver, is unknown. 117 Spleen Active coeliac disease affects the immune system as a whole, a phenomenon most clearly confirmed by evaluation of spleen size and function.…”
Section: Livermentioning
confidence: 99%
“…105,106 Increased levels of liver function enzymes can be observed in nearly half of the patients with coeliac disease at diagnosis. [107][108][109][110][111][112] Although these abnormalities are generally subclinical, coeliac-diseaserelated liver injury can progress to cirrhosis and liver failure. 113 In epidemiological data, patients with coeliac disease have a twofold to sixfold increased risk of future liver disease, and an eightfold increased risk of death from liver cirrhosis.…”
Section: Livermentioning
confidence: 99%
“…Serum aminotransferase elevations will normalise with the removal of gluten from the diet, suggesting a causal relationship between gluten intake and intestinal damage and liver injury. A recent review demonstrated elevated liver function tests, specifically AST and ALT, in 40.6% of patients with untreated coeliac disease compared with 24.2% of treated patients and 16.6% of matched controls …”
Section: Liver Function Test Resultsmentioning
confidence: 99%